KRISTAL HEMOGLOBIN PADA BERCAK DARAH YANG TERPAPAR BEBERAPA DETERJEN BUBUK KHUSUS MESIN CUCI MENGGUNAKAN TES TEICHMANN DAN TES TAKAYAMA - Vitriani, Viras; Asni, Enikarmila; Indrayana, Mohammad Tegar (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBloodstains are evidence which might be found in the scene of crime cases. However, the bloodstains are not always found intact as a result of criminal’s attempt to destroy the evidence by using cleaning agent for example detergent. The bloodstains which have been contaminated by detergent might give a different forensic examination result. This study has an aim to determine the formation of hemoglobin crystal on contaminated bloodstain using Teichmann test and Takayama test. In this study, there were five powder detergent solutions flowed onto bloodstained slides for each tests. The result shows that all 11 slides (100%) still have positive result which means the hemoglobin crystal still can be found in the contaminated bloodstain using Teichmann test and Takayama test. The conclusion of this study is the detergent powder for washing machine that used might not affect the formation of hemoglobin crystal using Teichmann test and Takayama test..Kata kunci: Bloodstain, detergent powder, hemoglobin crystals, Teichmann test, Takayama test.